Insulin resistance assessed by estimated glucose disposal rate is associated with all-cause and cardiovascular mortality among postmenopausal women - Qian, Han; Chai, Dayang; Zhao, Shouming (Frontiers in Endocrinology, 2025)
PurposeThe estimated glucose disposal rate (eGDR) is a noninvasive and practical marker for assessing insulin resistance, but its association with mortality in postmenopausal women remains uncertain.MethodsA cohort of 9371 postmenopausal women from the National Health and Nutrition Examination Survey (1999-2018) was studied. Baseline eGDR was calculated, and mortality outcomes (all-cause and cardiovascular) were linked to National Death Index (NDI) records up to December 31, 2019. Multivariate Cox regression, restricted cubic splines, and subgroup analyses were employed to assess the relationships between eGDR and mortality.ResultsDuring a median follow-up of 98 months, 2151 deaths from all causes and 679 from cardiovascular causes were documented. In the multivariable-adjusted Cox model, higher eGDR quartiles were associated with progressively lower all-cause and cardiovascular mortality. In comparison to the lowest eGDR quartile, the highest quartile showed adjusted hazard ratios of 0.765 (0.646-0.906) for all-cause mortality and 0.677 (0.498-0.921) for cardiovascular mortality. A U-shaped relationship between eGDR and all-cause mortality was identified, with an inflection point at 5.11 mg/kg/min. Subgroup analyses revealed a stronger association between eGDR and all-cause as well as cardiovascular mortality in individuals younger than 60 years.ConclusionsAmong postmenopausal women, decreased eGDR, signifying higher insulin resistance, correlates with greater risks of all-cause and cardiovascular mortality.